Effects of oil extraction from Moringa oleifera seeds on coagulation of turbid water - Muyibi, Suleyman Aremu; Megat Mohd. Noor, Megat Johari; Leong, Tan Kok; Loon, Lam Hong (Taylor and Francis, 2002)
In this study the results of laboratory based investigation into the effects of extracting oil from Moringa oleifera on its coagulation effectiveness using turbid water samples from two rivers are presented. Samples of raw water were taken from Sungai Selangor Water Treatment Plant at Batang Berjuntai and Sungai Semenyih Water Treatment Plant in Kuala Lumpur, Malaysia. The turbidities of the water samples from the two sources varied from 56 to 451 NTU. For water sample with initial turbidity of 451 NTU, shelled oil extracted Moringa oleifera was able to achieve 98% turbidity removal at an optimum dosage of 200 mg/l compared to 96.9% obtained at optimum dosage of 300 mg/l using the shelled blended. For the low turbidity of 56 NTU, shelled oil extracted Moringa oleifera achieved 87% turbidity removal at 250 mg/L optimum dosage whilst shelled blended was able to achieve 81%. The oil extracted from the Moringa kernel was up to 35% per kernel weight.